Analysis of Helical Gear Failure in Off-Road 4x4 Gearbox - Husaini, Husaini; Darmawan, Haris; Ali, Nurdin - (Politeknik Negeri Lhokseumawe, 2024)
Surface failure is evident in helical gear in off-road 4x4 gearbox,requiring the identification ofroot causes.Therefore, this study aimed to explore the factors contributing to helicalgearfailure in off-road 4x4 vehicles. Initially, crack in helical gear wascaused by manufacturing or material defects during production or the heat treatment process, manifesting as inhomogeneities in the microstructure or other imperfections. Crack propagation possibly occurred due to continuous stress during off-road 4x4 usage, influenced by factors such as excessive loads, vibrations, or extreme off-road conditions.The exploration process began with a comprehensive set of analyses, including visual observation, hardness testing, chemical composition analysis, microstructure testing, and stress analysis. Subsequently, the material composition of gear was identified as high-carbon steel meeting AISI 1080 standards. Although the average surface hardness value was 95.49 HRB, which was slightly lower than AISI 1080, the microstructure comprised pearlite and cementite. Surface fracture observations revealedinitial crackthat propagated, leading to brittle fractures. The average stress intensity factor (KI)was alsomeasured 54.65 MPa.m1/2, which surpassed fracture toughness value (KIC) of AISI 1080 steel at 45.5 MPa.m1/2.In conclusion, helical gear failure was directly attributed to the propagation of initial crack, thereby resulting in fractures.